2006
DOI: 10.1377/hlthaff.25.2.348
|View full text |Cite
|
Sign up to set email alerts
|

The Costs Of Scaling Up Vaccination In The World’s Poorest Countries

Abstract: We examine the relationship between country-level average costs and coverage levels for diptheria-pertussis-tetanus (DTP) vaccines. Coverage data are from the World Health Organization, and cost data are from financial sustainability plans filed with the Global Alliance for Vaccines and Immunization (GAVI) by forty countries from 2000 to 2003. In this data set, average costs are lower for countries that vaccinate more children. At the highest numbers of covered children, there was no trend toward higher averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 1 publication
3
17
0
Order By: Relevance
“…Second, this study shows that system costs of immunization programs at the facility level range widely, and that these costs are tightly correlated with the number of vaccine doses delivered. Similar findings on the range in unit costs in different health service settings have been reported for Peru [16] and for many other developing countries [17]. Additional studies are required to determine how much of the observed range at the facility level is unavoidable, and how much represents an opportunity to improve efficiency.…”
Section: Discussionsupporting
confidence: 70%
“…Second, this study shows that system costs of immunization programs at the facility level range widely, and that these costs are tightly correlated with the number of vaccine doses delivered. Similar findings on the range in unit costs in different health service settings have been reported for Peru [16] and for many other developing countries [17]. Additional studies are required to determine how much of the observed range at the facility level is unavoidable, and how much represents an opportunity to improve efficiency.…”
Section: Discussionsupporting
confidence: 70%
“…for Zambia's higher costs, although factors such as wastage, coverage and vaccination completion rates may also contribute to differences. Results provide a new reference point for labour costs after remuneration increases aimed at strengthening human resources for health, as well asconfirming labour intensity of immunization programmes found by previous studies[19].Findings also show the relative importance of other delivery costs and vaccines in the current context. Even if all staff costs are removed, Zambian unit costs remain close to higher previous unit cost estimates.…”
supporting
confidence: 69%
“…[23][24].Several, costing studies have found that that factors such as service volume, number of immunization sessions, immunization strategy and prices affect total vaccination program cost[9][10][21][22][23][25][26]. Others have shown a strong, negative association between scale of services and unit costs[19]. A statistical analysis of immunisation costs in PHC facilities in India found a significant positive association between total facility cost and not only the number of doses administered, but also production factors such as type of vaccination strategy[25].…”
mentioning
confidence: 99%
“…However, the corresponding increasing marginal costs may not apply at all coverage levels. In fact, economies of scale and network externalities could play a role at higher coverage levels, leading to locally concave cost functions [31]. Examples of cost-function level curves in a fixed-resource setting where C ( υ m , υ f ) = K for some K > 0, are found in Figure 2a.…”
Section: Model Description and Validationmentioning
confidence: 99%